DESIGNING COASTAL-STYLE BATIK FROM LASEM: THROUGH STYLIZATION BASED ON TREND FORECASTING - Ardiyansyah Mega Sejati; Achmad Nur Kholis (JURNAL IMAJINASI, 2026)
Trend development is part of the industrial world, especially in fashion and textile production. Every period has changes in public interest regarding patterns, colours and styles in fashion. These changes must also be followed by the traditional textile industry such as the batik business. The utilisation of trend forecasting can be applied to artisans in various regions, such as in Lasem, which is known for its unique pesisiran-style motifs. The purpose of this research is to increase the diversification of Batik Lasem products using trend forecasting. The method used is art-based research, where the process of creating batik as an art product is supported by the data collection process. Some of the data collection techniques used are interviews, observations, and literature review. The result of the research found that the main characteristic of Lasem Batik is the coastal style that emphasises the typical visuals of coastal areas which are also influenced by Chinese culture. The natural and cultural potential is transformed into a motif with the Deep Blue Sea team that is attached to the Lasem regional identity. The process of transforming the source of ideas into visuals is made on the basis of trend forecasting, with the aim of increasing potential market interest.